2004
DOI: 10.2165/00129784-200404010-00003
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin Inhibitor-Associated Early Renal Insufficiency in Cardiac Transplant Recipients

Abstract: Cardiac transplantation is the definitive treatment for eligible patients with end-stage cardiac failure. Techniques have evolved to reduce surgical mortality to under 5%. Immediate and subsequent long-term survival is more dependent on acute and chronic rejection and the complications of immunosuppressive therapy. Ten-year survival is greater than 50%.The success of transplantation over the last 20 years has been largely due to the advances in immunosuppression. The most notable and dramatic milestone was the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
28
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 55 publications
0
28
0
Order By: Relevance
“…However, while we observed that a single injection with FK506 improved fear conditioned memory function in Tg2576 mice, prolonged treatment of humans with FK506 has been reported to be associated with significant side effects, most notably nephrotoxicity (Olyaei et al, 2001;Baran et al, 2004;Staatz and Tett, 2004). Therefore, before considering clinically attractive the idea of CaN inhibitors for treating AD, future studies will have to determine whether lower, less nephrotoxic doses of FK506 administered for longer periods of time still provide behavioral benefits or whether novel behaviorally-active drugs that selectively target only CaN in the CNS could eventually be designed.…”
Section: Discussionmentioning
confidence: 76%
“…However, while we observed that a single injection with FK506 improved fear conditioned memory function in Tg2576 mice, prolonged treatment of humans with FK506 has been reported to be associated with significant side effects, most notably nephrotoxicity (Olyaei et al, 2001;Baran et al, 2004;Staatz and Tett, 2004). Therefore, before considering clinically attractive the idea of CaN inhibitors for treating AD, future studies will have to determine whether lower, less nephrotoxic doses of FK506 administered for longer periods of time still provide behavioral benefits or whether novel behaviorally-active drugs that selectively target only CaN in the CNS could eventually be designed.…”
Section: Discussionmentioning
confidence: 76%
“…13) Recent studies have suggested that switching CNI to EVL can spare renal function in HTx and renal transplantation recipients. 10,14,15) We consistently found that reducing the dose of CNIs along with administration of EVL improved renal function in the present case.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15][16] The risk of ESKD in adult SOT recipients varies by organ transplanted. 4 This variability may be explained by differences in the burden of baseline comorbidities, variations in intensity of immunosuppressive regimens, and distinct rates of peritransplant AKI.…”
mentioning
confidence: 99%